Sustainable development goal policy / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
UiTM has taken into account the actions needed to respond to the environmental objectives that can be integrated into the SDG and its core business.